“ELABORACIÓN DE UNA GUÍA DIDÁCTICA PARA EL APRENDIZAJE DE QUÍMICA ORGÁNICA CON LOS ESTUDIANTES DE TERCERO DE BACHILLERATO GENERAL UNIFICADO DE LA UNIDAD EDUCATIVA VIGOTSKY, PERIODO ABRIL- AGOSTO 2019” - Malo Patiño, Paul Rodrigo (2020)
This research was carried out in the “Vigotsky” Educational Unit, which began its pedagogical work 14 years ago, with the levels Initial to First level of Basic Education in the central campus and in the year 2016 it started whit the Unified General Baccalaureate. The aim was to propose the use of a didactic guide for the learning of Organic Chemistry. In the Vigotsky Educational Unit there is a no a pedagogical guide for the teaching of Organic Chemistry, in the 2018-2019 school year whit the students of the Third y Year of the Unified General Baccalaureate, so the lack of interest in studying Organic Chemistry is evidenced, for this reason, this research proposes a didactic guide of this subject. The design of the research used was: non- experimental, the type of research was field and bibliographic, the level of search: diagnostic. The method applied was: inductive, deductive. By organizing the results of the investigation, it was determined that the students respond better whit practical activities and not only whit pedagogical activities. In addition, it is important to mention that the conservative or traditional model that has been imposed by the Ministry of Education of Ecuador for many years for the learning of Organic Chemistry has several limitations.